Prawodawstwo Konferencji Episkopatu Polski i Prymasa kard. S. Wyszyńskiego w zakresie sakramentów w służbie wspólnoty : święceń i małżeństwa - Janczewski, Zbigniew (Prawo Kanoniczne, 1999)
Two sacraments: the order and the marriage arc very difficult for the social life o f the Church. This article shows the legislation of the Conference Episcopate of Poland and the polish primate cardinal Stefan Wyszyński in the scope of those sacraments. Primate Wyszyński was lawgiver on the all Church in Poland, because he had extraordinary licenses from the Holy Sec. The Conference Episcopate and the primate was promulgating manylegal acts about the sacraments.